2019
DOI: 10.3889/oamjms.2019.390
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Result of Arthroscopic Anterior Cruciate Ligament Reconstruction Using Anterior Half of Peroneus Longus Tendon Autograft

Abstract: BACKGROUND: Anthroscopic anterior cruciate ligament reconstruction is one of the most successful operations in sports medicine. At present, ligament autografts have been the best method due to good histocompatibility, rapid healing, no cross-contamination, and low cost of treatment. However, autografts do not have infinite amount and are also not always feasible. Anterior half of peroneus longus tenden autograft is likely to become a source of autograft with many advantages. This study aims to evaluate the cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…These findings are similar to Shao's research, which calculated a general decrease of 22% of inversion and eversion strength after the use of full thickness peroneal grafting albeit the lack of ankle joint instability 16 . Their research conflicted with Liu and Trung's study to a certain extent, since they stated that none of their patients complained of ankle joints instability after they utilized only the anterior half of the peroneus longus tendon 6,17 . Further research might be needed since the fundamental difference about them is how only half PLT grafts were used instead of full thickness PLT grafts 2,6,16,17 .…”
Section: Correlation Of Anthropometric Features With Peroneus Longus mentioning
confidence: 84%
See 1 more Smart Citation
“…These findings are similar to Shao's research, which calculated a general decrease of 22% of inversion and eversion strength after the use of full thickness peroneal grafting albeit the lack of ankle joint instability 16 . Their research conflicted with Liu and Trung's study to a certain extent, since they stated that none of their patients complained of ankle joints instability after they utilized only the anterior half of the peroneus longus tendon 6,17 . Further research might be needed since the fundamental difference about them is how only half PLT grafts were used instead of full thickness PLT grafts 2,6,16,17 .…”
Section: Correlation Of Anthropometric Features With Peroneus Longus mentioning
confidence: 84%
“…Their research conflicted with Liu and Trung's study to a certain extent, since they stated that none of their patients complained of ankle joints instability after they utilized only the anterior half of the peroneus longus tendon 6,17 . Further research might be needed since the fundamental difference about them is how only half PLT grafts were used instead of full thickness PLT grafts 2,6,16,17 . Thus, it might be compulsory for patients who prefer to use this graft to undergo monitoring and rehabilitation in that period in order to reduce the morbidity.…”
Section: Correlation Of Anthropometric Features With Peroneus Longus mentioning
confidence: 84%
“…The assessment on ankle plantar flexion and foot eversion muscle strengths showed normal function. A report on ACLR using anterior half PLT graft showed no complications in ankle and foot post-surgery [ 15 ]. Another study revealed enhancement on knee functionality based on the Lysholm and KT-3000 arthrometer scores, leaving no ankle functionality differences based on AOFAS score [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Autologous peroneal longus tendon has recently been used as a graft to reconstruct injured ligaments [16][17][18] . In contrast with semitendinosus tendon and gracilis tendon, PLT is easier to be taken off for its super cial location and no ber connection with nearby tendons or deep fascia [18] .…”
Section: Discussionmentioning
confidence: 99%